Philosophy of clinical neurosurgery - Leonid B. Likhterman (LLC "MEDIAFORMAT", 2022)
Philosophical enquiry of the founders of neurosurgery is reflected. Practical implementation of neurosurgical philosophy through clinical thinking and conceptual approaches to surgical interventions on the brain and spinal cord is described. The issues of ethics and humanism in neurosurgery feature prominently together with the analysis of the contradictions identified and the ways of dealing with them. The importance of philosophical positions in developing a new field, the preventive neurosurgery, is substantiated. It is found that these are philosophical approaches that allow preserving the integrity of neurosurgery as a single clinical discipline in the context of the increasing technologization and differentiation, as well as implementing the systematic approach to the patient. The "tree of philosophy of neurosurgery" is developed and presented.